192k views
3 votes
Simply and show how you got the answer

Simply and show how you got the answer-example-1
User Igofed
by
5.7k points

1 Answer

0 votes

Solution:

Problem 1.


(3)/( √(5) - 2 )

Rationalize the denominator by multiplying the numerator and denominator by the denominator. (Important: if the denominator has a minus sign, change to plus and vice versa)


⟹(3 * √(5 + 2) )/( (√(5) - 2 ) * ( √(5) + 2) )


⟹ (3 √(5) + 6 )/( √(25) + 2 √(5) - 2 √(5) - 4 ) ⟹(3 √(5) + 6 )/(5 - 4)


⟹(3 √(5) + 6)/(1) ⟹3 √(5) + 6

Problem 2.


(6 - √(12) )/( √(3) + √(10) )

Rationalize the denominator.


⟹((6 - √(12) ) * ( √(3) - √(10) ))/( (√(3) + √(10) ) * ( √(3) - √(10) )


⟹(6 √(3) - 6 √(10) - √(36) + √(120) )/( √(9) - √(30) + √(30) - √(100) )


⟹ (6 √(3) - 6 √(10) - √(36) + √(120) )/(3 - 10) ⟹ (6 √(3) - 6 √(10) - √(36) + √(120) )/( - 7)


⟹(6 √(3) - 6 √(10) - 6 + √(12 * 10) )/( - 7)⟹(6 √(3) - 6 √(10) - 6 + 4 √(3 * 10) )/( - 7)


⟹ - (6 √(3) - 6 √(10) - 6 + 2 √(30) )/(7)

Therefore:

1.
3 √(5) + 6

2.
- (6 √(3) - 6 √(10) - 6 + 2 √(30) )/(7)

I hope these help

User Sinju Angajan
by
5.3k points